The Use of Prehistoric Cave Animation Videos as a Learning Media Based on Critical Thinking Skills - Makawi, Faizal Erlangga (Equilibrium: Jurnal Pendidikan, 2026)
This study aims to examine in depth the effectiveness of using prehistoric cave painting animation videos as a learning medium in enhancing students’ critical thinking skills, active engagement, and understanding of cultural context in art education at the secondary school level. The study employed a mixed-method approach involving 20 students who were purposively selected as participants. Data were collected through observations, written tests, and in-depth interviews to obtain a comprehensive understanding of both the learning process and outcomes. The analysis was conducted using the Conceptual Framework (artist, artwork, world, and audience), The Four Frames (subjectivity, cultural, structural, and postmodern), and Cognitive Load Theory to understand the dynamics of students’ cognitive processes. The results indicate a significant improvement in students’ analytical writing skills, classroom engagement, and understanding of cultural values embedded in artworks. In addition, students demonstrated stronger critical reflection and a high level of cognitive retention. These findings confirm that animation-based learning is effective not only as a visual medium but also as an integrative pedagogical approach.